2015
DOI: 10.3892/etm.2015.2441
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum leptin levels and peritoneal dialysis: A meta-analysis

Abstract: Abstract. There is limited information available with regard to the association between serum leptin levels, or other adipokines, and serum lipid levels and insulin sensitivity in patients undergoing peritoneal dialysis (PD). Thus, the aim of the present study was to perform a meta-analysis investigating this association. Potential relevant studies were identified through searching the following databases: MEDLINE, Science Citation Index, Cochrane Library, PubMed, Embase, CINAHL, Chinese Biomedical, Chinese Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Our results support recent studies regarding the importance of leptin levels in PD patients. As well as the majority of previous studies [9,[16][17][18][19] the results of our study have demonstrated an increasing level of serum leptin concentration in ESRD patients after PD treatment initiation. Teda D et al showed that a single 6-h dwell with PD4 3.86% glucose acutely increased plasma leptin level [20].…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Our results support recent studies regarding the importance of leptin levels in PD patients. As well as the majority of previous studies [9,[16][17][18][19] the results of our study have demonstrated an increasing level of serum leptin concentration in ESRD patients after PD treatment initiation. Teda D et al showed that a single 6-h dwell with PD4 3.86% glucose acutely increased plasma leptin level [20].…”
supporting
confidence: 86%
“…Distinctively ever-increasing serum leptin level in overweight PD patients can be a consequence of altered glucose and fat metabolism which may lead to chronic inflammation, malnutrition and low long-term survival of the patients [17,18]. On the other hand, hyperleptinemia is reported as the phenomenon of "Reverse Epidemiology" or "Obesity Paradox" in patients with ESRD [22,23].…”
mentioning
confidence: 99%
“…The glucose concentration of different dialysis buffers may impact the burden of kidney filtration rate [11]. Studies have shown that the glucose concentration also promotes peritoneal inflammation and the production of transforming growth factor by peritoneal mesothelial cells, finally leading to fibrosis [12]. Therefore, peritoneal dialysis combined with FIR can reduce the side effects of glucose in dialysis buffer, which interferes with peritoneal inflammation and peritoneal mesothelial cell fibrosis.…”
Section: The Physiological Effect Of Peritoneal Dialysis Due To Firmentioning
confidence: 99%
“…Glucose degradation products (GDPs) contribute to reduced dialysis function and the pathogenesis of peritoneal membrane fibrosis [8,9,10]. A previous study showed that long-term exposure to non-biocompatible high-concentration glucose dialysate and repeated peritonitis are the main causes of changes in the structure and function of the peritoneum [4,11,12]. In summary, these factors induce proinflammatory hormones, such as interleukin-l beta (IL-1β), interleukin(IL), and tumor necrosis factor alpha (TNF-α), which triggers a persistent inflammatory response in the peritoneum, ultimately leading to structural changes in the peritoneum [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose degradation products (GDPs) contribute to reduced dialysis function and the pathogenesis of peritoneal membrane fibrosis [ 8 , 9 , 10 ]. A previous study showed that long-term exposure to non-biocompatible high-concentration glucose dialysate and repeated peritonitis are the main causes of changes in the structure and function of the peritoneum [ 4 , 11 , 12 ]. During an acute inflammatory process such as peritonitis, natural killer (NK) cells produce inflammatory cytokines such as tumor necrosis factor alpha (TNF-α) and interleukin (IL-6).…”
Section: Introductionmentioning
confidence: 99%